PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR BARISAN DAN DERET MATEMATIKA KELAS XI SMAN 1 MEULABOH - Irma Tiarina; Syarifah Merya; Anita Tiara (Jurnal Dedikasi Pendidikan, 2024)
Teachers as educators need to use appropriate learning models in delivering material to students to achieve optimal learning outcomes. A learning model that can be implemented to help students relate theory to real life, namely Problem-Based Learning (PBL). This research aims to determine the effect of PBL on learning outcomes of mathematical sequences and series. This research is a quantitative experiment using a pre-experimental one group pretest-posttest design method with sequence and series story questions as instruments. The population in this study was 206 students in class The data analysis used in this research is descriptive statistics and inferential statistical analysis (Wilcoxon). The results of the Wilcoxon analysis showed that the results of applying the problem based learning model to the learning outcomes of mathematical sequences and series were p 0.000 < 0.05. So it can be concluded that there is an influence of applying the problem based learning model on improving learning outcomes of mathematical sequences and series. It is recommended that teachers apply the problem based learning model in mathematics or other subjects